Anti-inflammatory, antioxidant and wound-healing effects of mad honey in streptozotocin-induced diabetic rats. Issue 4 (7th August 2020) - Malkoç, Meltem; Yaman, Serap Özer; Imamoğlu, Yasemin; İnce, İmran and Kural, Birgül Vanizor and Mungan, Sevdegül and Livaoglu, Murat and Yıldız, Oktay and Kolaylı, Sevgi and Orem, Asım
Abstract : Mad honey or rhododendron honey containing grayanotoxins possesses antioxidant and anti-inflammatory properties. This study was planned to evaluate the effects of topical application of mad honey on wound healing in diabetic rats. Dorsal skin wounds were created under anesthesia in male Wistar albino rats with streptozotocin-induced diabetes mellitus randomly divided into three groups (each n = 28). Group I received topical 0.09% saline solution, Group II received terramycin, and Group III received mad honey. Wound tissues were collected after decapitation on days 3, 7, 14, or 19 post-wounding. Levels of malondialdehyde (MDA), and activities of the antioxidant enzymes superoxide dismutase, glutathione peroxidase, and catalase were determined using quantitative methods. Gene expressions of the inflammatory markers such as tumor necrosis factor alpha (TNF-α) and metalloproteinase 9 (MMP-9) and of the anti-inflammatory marker interleukin-10 (IL-10) were analyzed using real-time reverse transcription polymerase chain reaction. Wound tissues were also subjected to histopathological examination. Significantly lower MDA levels and TNF-α and MMP-9 expression, and increased antioxidant enzyme activities and IL-10 expression were observed in the mad honey group (Group III) compared with Group I. These parameters exhibited similar changes in Group II compared with Group I. In conclusion, the topical use of mad honey improves the healing of diabetic wounds in examined rats.